Peningkatan Kompetensi Multimedia Bidang Fotografi Melalui Workshop Photopreneur - Pramudhita Ferdiansyah; Citra Desy Aisyah Alkis (Universitas Muria Kudus, 2020)
Multimedia is an important aspect to support the economy and business nowadays. The knowledge owned by a student gives a big influence on the multimedia department. The work of multimedia products has great value. Photography is classified as part of multimedia science which attracts a lot of interest because of social media growth. Many people think that photography is just for social media attraction. Only a few people know that photography can be used to get an economic advantage from the internet. Most of them think that they need fancy and expensive gear to get good photos and make money from it. PKM or student activities to improve the ability of the community that we do is to provide a photography guide to the multimedia department in technical schools or vocational schools. The PKM team provided the knowledge that any photo can be sold without using the expensive gear. The training begins with the theoretical base and then continues with practical work. The lessons given are the composition of photography, field practice, photo editing, and sending photos to microstock agents. We also give them some tips and trick to make their photos accepted by the microstock agents. The results of this training are providing an increase in knowledge for the participants. As many as 53% of participants can send photos and accepted by microstock agents. 83% of the participants can master photo processing software. Can be concluded that after the training, most of the participants can master the composition of photos, editing, and sell their photos to microstock agents.